Sharīa scripts a historical anthropology - Messick, Brinkleye (Columbia University Press, 2018)
In the first half of Sharīʻa Scripts, Messick looks at the principal types of theoretical or doctrinal juridical texts, which are collectively referred to as the "library," while those of the second half, including the genres produced by the sharīʻa courts and by notarial writers, are termed the "archive." Messick demonstrates the analytic significance of sustained attention to the textual form of written sources such as the doctrinal works, juridical opinions, court records and legal instruments studied here. He suggests that attention to form should be a precondition for wider research, for properly assessing the import of conventional source content, for the writing of history. Messick looks at historical sharīʻa through a particular instance, that of highland Yemen in the first half of the twentieth century. Yemen, of course, is an integral region of the Arabic-speaking heartlands of Islam, and the Zaydī school of jurisprudence that is the specific focus of the book has been rooted there for a millennium. Elsewhere in the same period, colonial regimes and nationalist reformers had begun to alter the political, societal and epistemic existence of the sharīʻa. They acted to replace its criminal, commercial and real estate provisions with western law, and effectively narrowed its sphere of relevance to matters of personal status and family law. In contrast, under the twentieth-century Zaydī imams the sharīʻa remained uncodified; highland sharīʻa courts maintained their historically broad competence; madrassa-trained judges employed classical sharīʻa rules of procedure and evidence; and archives had yet to upended by western-style standards of file-keeping and printed forms